Metode Elektrokoagulasi Untuk Mengolah Limbah Cair Batik Di Unit Kegiatan Masyarakat Rumah Batik Andalan PT. Riau Andalan Pulp And Paper (RAPP) - Yunitasari, Yonna; Elystia, Shinta; Andesgur, Ivnaini (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Batik wastewater have color contents as naphtol, indigosol, and remazol which is streamed directly to the environment without treatment can decrease environment quality because batik wastewater consist heavy metals, suspended solids, and organic matters. Batik wastewater can be treated by electrocoagulation method. These research targets are to determine the removal efficiency of TSS and pH, compare to the quality standard, and knowing the effect of voltage and contact time. The electrocoagulation basin reactor is made in 30 cm x 25 cm x 25 cm of dimentions with total volume of wastewater is 10 L, using aluminium electrode plates with size of plate is of 17 cm x 17 cm, the plate thickness is 3 mm the distance between plates is 1 cm. The variabele of research are voltage (10, 15, and 20 volts) and contact time 30, 45, and 60 minutes. The result showed that the most efficient is 20 volts of voltage 60 minutes of contact time. The percent removal for TSS is 99,11% with concentration of effluent is 11 mg/L. The pH value is 11,2. Based on the result TSS parameter already complied the standard of PERMENLH/5/XLII/2014, except pH parameter.Keywords: Aluminium, electrocoagulation, batik wastewater, voltage, time contact.